What We Ask of Others: Ethics on the Record, Institutional Power, and Moral Practice in a Fractured World - Swana, Matimba; Shah, Niyoshi (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2026)
In a time of political hostility, deepening inequality, and growing distrust in public health systems, bioethicists must ask what it means to be moral actors across borders. This reflection draws on Ethics in Practice, a podcast series that captures personal stories of moral conviction and action in the field of global health research. Across five episodes, our guests reflected on what it means to uphold ethical values, such as justice, solidarity, and self-accountability in the face of institutional barriers, power asymmetries, and moral injury. This commentary focuses on the broader effort of the podcast: to make visible the everyday struggles and subtle resistance of those trying to be good within complex systems. As such, the podcast is positioned as a deliberation on and an expression of ethical action, for it not only uses storytelling to explore moral complexity but also to create moral space. We have used excerpts from the podcast episodes to highlight ethical challenges and collaborative solutions in bioethics. We explore the “underdeveloped aspect” of a bioethicist’s role and argue for a practice of ethics that is relational, imperfect, and guided by moral imagination. It is both a challenge and an invitation for bioethicists in the US, Canada, and other countries to stand in moral solidarity across borders. Amid collective grief and systemic harm, we are called to show up for one another, not just in principle, but in practice.